(untitled) (Indian Journal of Animal Production and Management, 2024)
Present study was carried out to assess the effect of parturition on feeding behaviour on before calving. 21 Kankrej cows were equally grouped into 3 treatments, first parity (T1), second parity (T2) and 3 or more parity (T3) cows. The behaviour of cows was recorded with two CCTV cameras and 24 hours’ observations were made from recorded video for four days −1, −2, −3 and −7 prior to the calving. The feeding behaviour was assessed in terms of feeding frequency, feeding duration and watering frequency. The mean feeding frequency was the highest on the day of calving (30.33±2.07) followed by day-3 (26.62±1.43), day-2 (25.33±1.46) and Day-7 (24.43±1.40) in a day and the difference found was significant (P<0.05). The mean feeding duration (min) was the minimum on the day of calving (273.19±14.45) followed by day-7 (315.00±11.17), day-2 (315.57±9.84) and day-3 (318.10.95±1.40) in a day and the difference found was significant (P<0.05). Mean water drinking frequencies was maximum on the day of calving 4.14±0.55 compared to 3.95±0.51, 3.67±0.40 and 3.81±0.48 on −2, −3 and −7 prior to the calving, respectively, but the difference found was not significant. Hence, it may be concluded from the study that cows have higher feeding frequency, less feeding duration and higher watering frequency on the day of calving than 2-7 days before the calving. The decrease in feeding duration on the day of calving is directly related to lesser feed intake and reason might be due to increase restlessness and discomfort associated with the parturition process.